Ionic Liquid-Carbon Nanomaterial Hybrids for Electrochemical Sensor Applications: a Review. (1st March 2016) - Abo-Hamad, Ali; AlSaadi, Mohammed AbdulHakim; Hayyan, Maan; Juneidi, Ibrahim; Hashim, Mohd Ali
Graphical abstract: Abstract: During the last decade, ionic liquids (ILs) have received a considerable attention in different fields of nanotechnology applications. Their unique physicochemical properties have been highly utilized in electrochemistry, commonly in the form of IL-carbon nanomaterial (IL-CNM) hybrids. The synergistic combination of both components results in significant improvement for numerous electrochemical applications, including energy storage devices and sensor electrodes. The need for high surface area, excellent electrical conductivity, high sensitivity, and catalytic activity was the key behind the extent of ILs usefulness and numerous applications. This review aims to provide an overview of the synthetic routes for electrochemical sensor fabrication based on IL-CNM hybrids. The differences in sensing performance between the electrode designs are also discussed. ILs can affect the structure and surface chemistry of CNMs, including carbon nanotube, graphene, and fullerene. IL-CNM-modified solid electrode was the most common and effective design used in academic research. However, the inclusion of biological components and metallic nanoparticles significantly affects electrode performance. The electrochemical techniques used for detection have varied based on several considerations related to electrode design and targeted analyte. They also play an important role in determining the sensor sensitivity and detection limit.